Are health hubs the future?. (2nd July 2019) - Jackson, Ian
Abstract : A new report, Fit For The Future, states that GP practices will need to evolve into 'wellbeing hubs' to meet patients' primary healthcare needs. Ian Jackson looks at what this means for GP surgeries, and what needs to change